Nanoporous α-Alumina Membranes with Pore Diameters Tunable over Wide Range of 30-350 nm. (18th September 2015) - Asoh, Hidetaka; Masuda, Tatsuya; Ono, Sachiko
Abstract : Nanoporous and α-alumina membranes with pore diameters tunable over a wide range of approximately 30–350 nm were successfully fabricated by optimizing the conditions for anodizing, subsequent detachment and heat treatment. Flat α-alumina membranes, each with a diameter of 25 mm and a thickness of approximately 50 μm, were obtained without thermal deformation. The present process is promising for fabricating free-standing and flat α-alumina membranes with various pore diameters; such membranes have potential technological and scientific applications in various fields.